(untitled) - Seager, Spencer L. (Belmont, CA, 2005)
Learn organic and biochemistry with ORGANIC AND BIOCHEMISTRY FOR TODAY with accompanying technology! With numerous allied health-related applications, examples, boxes, and a new Companion Web Site, GOB ChemistryNow, this chemistry text provides you with the tools you need to succeed. Explanations and examples show you the role of chemistry in your daily life. The online tool GOB ChemistryNOW will save you time and help you get a better grade by creating a personalized learning plan for you that targets your study needs and helps you to visual, practice, and master the material in the text.
Keywords: Chemistry, organic,Biochemistry